THE EVOLVING REPRESENTATION OF WOMEN IN DISNEY PRINCESSES - Indra Leitte Paula, Sonia (Universitas Negeri Semarang, 2020)
Many young girls across the globe lookup to Disney’s princesses. However, the princess images created by Disney carry gender-role stereotypes. Most stories have a stereotypical plot: the girl meets the prince; the prince falls in love with the girl, and the two get married and live happily ever after. The female characters are always portrayed as ordinary women who wish that a rich and handsome man will come and make their lives better. However, the images of Disney princesses have changed in the past eight years. Since 2012, Disney princesses have had more progressive female characters, as seen in Brave, Frozen, and Moana animated features. The main characters are different from past Disney princesses. This paper will try to analyze gender roles in contemporary Disney princesses